Psychotherapeutic interventions in families with children with disabilities: Principles and rationale of the ecosystemic psychodynamic model - Ε. Κουρκούτας, Ηλίας (Psychology: the Journal of the Hellenic Psychological Society, 2020)
The purpose of this paper is to present the development of family centered approaches and intervention models focusing on families with children with various forms of disability. In addition, the key principles, the rationale and the techniques of the psychodynamic ecosystemic model targeting families with children with particular difficulties or disabilities, will be presented. The present model aims at helping families and children with disabilities at risk for the development of secondary psychosocial disorders. Finally, intervention difficulties, as well as family problems that professionals working with this model are facing will be discussed.